A new class of anionic metallohelicates based on salicylic and terephthalic acid units, accessible in solution and by mechanochemistry. Issue 42 (26th April 2021) - Do, Jean-Louis; Titi, Hatem M.; Cuccia, Louis A.; Friščić, Tomislav
Abstract : We describe a new helicate design based on readily available, abundant salicylic and terephthalic acids, accessible in solution and mechanochemically. Abstract : We present a new class of anionic metallohelicates based on an abundant, industrially relevant salicylic acid derivative, leading to discrete double and triple-stranded architectures based on divalent and trivalent metals (Cu 2+, Fe 3+, respectively). The ability to assemble the metallohelicates in a solvent-free environment presents the opportunity to develop an inexpensive and environmentally-friendly design of helicate materials.